A laboratory simulation investigating the impact of sunglass tint on the catching performance of cricket fielders - Nellemann, Stacy Amanda (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Background: Sunglasses are popularly worn by outdoor athletes such as cricketers. They are primarily worn to preserve ocular health due to the length of time exposed to the sun's glare on the field. More recently, sunglasses are now worn for their purported performance-enhancing benefits supposedly allowing athletes to "see clearly, react faster and perform with confidence" . Fielders typically wear sunglasses, but it is rare to see the bowler or the batter wearing sunglasses although they are exposed to the same conditions. If sunglasses provide visual clarity for better reaction time, it is assumed this would also be beneficial for both batsmen and bowlers alike. It is interesting that although fielding plays a key role in the winning of a match, it has received very little research in comparison to the areas of batting and bowling. Research concerning sunglasses in the past has been concerned with its effect on ocular parameters such as colour vision and contrast sensitivity, with minimal research on their effect on performance, specifically on how different colour tints may affect performance such as catching in fielding. Objective: The purpose of this study was to compare the catching performance of fielders when wearing three different colour tints of sunglasses. Methods: Thirty male cricketers currently playing for Rhodes University or country districts sides in Makhanda, South Africa, who were non-habitual sunglass wearers were recruited for this study. An optician administered a pre-screening test to ensure participants did not have any visual defects that would affect the results, determining who was eligible to continue with the research project. Twenty-five participants qualified with a further four withdrawing during the experimentation phase due to personal reasons. Eligible participants were required to complete four testing sessions on separate days thereafter in which they wore a different colour tint at each session (clear, blue, G30 and red). These tints were randomised among participants. Participants were required to catch 18 balls projected from a bowling machine in each session. The number of balls caught as well as the quality of catch was recorded. At the end of the fourth session, participants were presented with a questionnaire investigating their subjective experience of the protocol and preference for any particular colour of lens. Results: Statistically significant results were found between the different colour lenses for the ocular parameters of contrast sensitivity and stereopsis tested by the optician. The red lens was found to be the best for contrast sensitivity with the blue lens performing the worst on this test. With regard to stereopsis, the G30 lens was the worst, with the red lens performing the best. The performance measures resulted in no significant difference between the different colour lenses both concerning the total number of catches taken as well as the quality of catch taken. The same result was found irrespective of the colour of lens used in each session. Data gathered from the questionnaire regarding visual comfort and target visibility resulted in the red lens being rated statistically worse than the other three conditions. In terms of personal preference, the G30 lens was rated statistically as the best coloured lens. Conclusion: It can be concluded that objectively there is no difference in performance between the three coloured lenses. Although from an ocular perspective, the red lens was expected to perform the best in terms of catching performance, there was no difference. Subjectively there was a strong preference among the players for the G30 lens with players strongly disliking the red lens.
Keywords: Sunglasses; Cricket -- Physiological aspects; Cricket players; Glare; Vision; Contrast sensitivity (Vision); Fielders (Cricket)